The Livelihood of Chinese Migrants in Timor-Leste - Ajito Fernandes (Social Sciences, 2022)
This article aims to describe, in depth, the experiences of migrant workers from China in maintaining their livelihoods in Timor-Leste through entrepreneurial activities before and during the COVID-19 pandemic. Specifically, this study discusses sustainable livelihoods with the knowledge of migration, adaptation, and entrepreneurship in Timor-Leste. To fulfill these aims, a qualitative methodology with a phenomenological approach was adopted by interviewing eight Chinese migrants who run businesses in Timor-Leste. Furthermore, the framework for the concept of sustainable livelihoods of the Department for International Development (DFID) was adapted to explain, in depth, the phenomena. The finding reveals that economic reasons encourage and attract Chinese migrant workers and entrepreneurs to Timor-Leste. The adaptation process of migrants in Timor-Leste relies on social capital to synergize with local communities in terms of culture, further affecting the comfort and security of entrepreneurship. From the perspective of sustainable livelihoods, migrant workers take advantage of human capital in the process of accumulation of financial capital to enhance their business activities. Meanwhile, migrant entrepreneurship expands their financial capital and human capital into social capital, physical capital, and natural capital. The findings also explain that the mobility and access to financial capital of Chinese migrants are supported through institutional structures, entrepreneurship activities, and policies. Furthermore, to ensure livelihood sustainability and business, Chinese migrants in Timor-Leste can carry out business intensification, extensification, diversification, and transformation strategies.